Simultanizam vremena? - Užarević, Josip (Array, 2000)
Simultaneity of Times If simultaneity should be determined as juxtaposition of two or more different (disparate) events or processes within the whole (persetputal act, text) in singular period of times - then such definition comes from presupossition that in the basis of simultaneous processes lies their affiliation with some common spatial or ontical complecs. It is especially provocative question for the thinker, if simultaniety of times is possible, i.e. one and same event should happen in to different (distant) times.